Evaluasi Pengelolaan Limbah Medis dalam Perspektif Quadruple Bottom Line: Studi pada RSUD H. Padjonga Daeng Alle - Fadil, Ahmad; Majid, Jamaluddin; Fajrin, Farid (Jurnal Ilmiah Akuntansi Peradaban, 2025)
This study aims to evaluate medical waste management in a RSUD H. Padjonga Daeng Alle using the Quadruple Bottom Line approach, encompassing environmental, social, economic, and governance dimensions. A qualitative case study method was employed, with data collected through interviews, observations, and document analysis. Data were analyzed using a descriptive-analytical approach based on the Quadruple Bottom Line framework. The findings reveal that medical waste management has complied with existing technical regulations but has not yet been integrated into a comprehensive sustainability system. Key weaknesses are identified in governance practices, limited environmental performance measurement, and the absence of systematic environmental cost management. These results highlight the importance of strengthening governance mechanisms and environmental accounting to support sustainable medical waste management in the public sector. Keyword: Sustainable Development, Medical Waste Management, Quadruple Bottom Line